Effect of ultrafine talc on crystallization and end‐use properties of poly(3‐hydroxybutyrate‐co‐3‐hydroxyhexanoate). Issue 45 (9th May 2016) - Vandewijngaarden, Jens; Murariu, Marius; Dubois, Philippe; Carleer, Robert; Yperman, Jan; D'Haen, Jan; Peeters, Roos; Buntinx, Mieke
ABSTRACT: Poly(3‐hydroxybutyrate‐ co ‐3‐hydroxyhexanoate) (PHBHHx) is a highly versatile polyhydroxyalkanoate. To enhance its slow crystallization, the performance of ultra‐fine talc (median diameter of 1 µm) as a nucleating agent is studied. This study focuses on crystallization, but also on the effect on fundamental properties (i.e., thermal stability) and selected end‐use properties (i.e., color, opacity, tensile properties, and gas permeability), to assess its applicability for food packaging purposes. Samples containing 0.5, 1, and 2 wt % were prepared through melt blending and compression molding. First, it was proven that ultra‐fine talc is a highly performant nucleating agent for PHBHHx. The isothermal crystallization half time at 70 °C was reduced to 97% by adding 2 wt % of talc, which could greatly improve the processability of PHBHHx. Thermal stability increased with 3–4 °C, due to increased barrier effect. Permeability for O2, CO2, and water vapor increased slightly upon addition of 0.5 wt % and 1 wt % talc, but decreased at 2 wt % talc. Nevertheless, the results remained within the same applicability range. An acceptable total color change of 0.9 was observed. Furthermore, the PHBHHx matrix was rendered stiffer (Young's modulus increased with 100 MPa), while showing hardly any change in elongation at break or tensile strength. Overall, it can be concluded that ultrafine talc is a very efficient nucleating agent for PHBHHx. Besides the beneficial effect on crystallization, the ultrafine talc hardly influenced any other property, which could prove to be of high added value for the application of these composites as food packaging material. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43808. Abstract :